Sustainability and Human Settlements : Fundamental Issues, Modeling and Simulations - M. Monto, L.S. Ganesh dan Koshy Varghese (Sage Publications, 2005)
This book—an outcome of the authors’ ongoing research on the complex relationships between humans and water in an urban context—presents an integrated model for assessing and forecasting the sustainability of human settlements, particularly urban communities. After introducing the conceptual and contextual dimensions of sustainability through an extensive review of the literature on the subject, the authors go on to explain their model. They then elaborate on the methodology for its formulation, development and implementation. This model has also been used to analyse changes in the availability of water and open spaces, and variations in lifestyles, community attitudes and living conditions including sanitation practices, and waste generation and its disposal.